Tackling Taboo Topics: A Review of the Three M s in Working Women’s Lives - Grandey, Alicia A.; Gabriel, Allison S.; King, Eden B. (Journal of Management, 2020)
In North America and Western Europe, women now compose almost half the workforce but still face disparities in pay and promotions. We suggest that women’s natural experiences of the three Ms (i.e., menstruation, maternity, and menopause) are taboo topics in ways that may constrain women’s careers. We propose that the three Ms are particularly incongruent with expectations at intersecting career stages (i.e., a job market newcomer having menstrual discomfort, an early career professional breastfeeding, a company leader getting hot flashes), with implications for work outcomes. In this review, we tackle the taboo of the three Ms by reviewing the evidence for how menstruation, maternity, and menopause are each linked to (1) hormonal and physiological changes, (2) societal beliefs and stereotypes, and (3) work affect, cognition, and behavior. We conclude by proposing novel implications for incorporating the three Ms into existing theoretical frameworks (i.e., work-nonwork spillover; stigma and disclosure; occupational health) and presenting new research questions and practices for understanding and addressing the ways that women’s health intersects with career trajectories.